1996
DOI: 10.1177/44.11.8918902
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring complex components laminin-5 and type VII collagen in intestine: association with migrating and differentiating enterocytes.

Abstract: Anchoring complex component laminin-5 and its subunits laminin (Ln)-alpha3 and Ln-beta3 chains, Type VII collagen, and integrin chains alpha3, alpha6, and beta4 were studied in developing and adult human intestine and compared with findings on Ln-alpha1 and Ln-alpha2 chains. In adult human duodenum, jejunum, and ileum, Ln-5 detected with a polyclonal antiserum and Ln-alpha3 and Ln-beta3 chains, detected with monoclonal antibodies (MAbs), were restricted to the epithelial basement membranes (BMs) of villi, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 24 publications
3
48
0
Order By: Relevance
“…However this expression of the transgene closely mimicked the endogenous mouse Col7a1 gene and similarly, COL7A1 mRNAs were found in equivalent human fetal tissues. These results are in broad agreement with immunohistochemical studies on adult human tissues, where low levels of collagen VII protein have been found in brain, 24 intestine, 22 urinary bladder and prostate, 21,23 endothelial cells, 25 and basement membranes surrounding or underlying the epithelia of the larynx, oesophagus, trachea, vagina and lung carcinoma. 20,21 The widespread expression of COL7A1 in internal organs may be characteristic of the fetal and neonatal state and faithful reproduction of the expression pattern by the transgene is of importance since internal epithelia are also affected in DEB.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However this expression of the transgene closely mimicked the endogenous mouse Col7a1 gene and similarly, COL7A1 mRNAs were found in equivalent human fetal tissues. These results are in broad agreement with immunohistochemical studies on adult human tissues, where low levels of collagen VII protein have been found in brain, 24 intestine, 22 urinary bladder and prostate, 21,23 endothelial cells, 25 and basement membranes surrounding or underlying the epithelia of the larynx, oesophagus, trachea, vagina and lung carcinoma. 20,21 The widespread expression of COL7A1 in internal organs may be characteristic of the fetal and neonatal state and faithful reproduction of the expression pattern by the transgene is of importance since internal epithelia are also affected in DEB.…”
Section: Discussionsupporting
confidence: 89%
“…1,[18][19][20] However despite reports of expression in other tissues, [20][21][22][23][24][25] the tissue range of expression of collagen VII has not been extensively studied in fetal and neonatal stages. To determine if the expression of the transgene in other sites was the result of inappropriate expression or was in parallel with a wide pattern of expression of the human gene, the presence of collagen VII mRNA in human 21-week fetal ( Figure 2b) and non-transgenic littermate mouse tissues ( Figure 2c) was examined and compared.…”
Section: Generation Of Transgenic Mice Expressing the Col7a1 Genementioning
confidence: 99%
“…Indeed, in the normal small intestinal mucosa, expression of laminin-5 and -10 is found to be restricted to the villus compartment (5,31,48). Interestingly, TNF-␣, IL-1␤, and TGF-␤ have been reported to be elevated in the entire CD mucosa, whereas IFN-␥ is mainly found at high levels in inflamed regions (19), supporting the possibility that TNF-␣ and IFN-␥ can also act synergistically in vivo.…”
Section: Discussionmentioning
confidence: 58%
“…Functional studies with human intestinal cells grown on purified laminin-2 and -10 showed that only laminin-10 has the ability to precociously induce villus-cell differentiation markers such as sucrase-isomaltase, thus confirming that distinct laminins can promote specific intestinalrelated gene expression (54). On the other hand, laminin-5 was found to be restricted to the differentiated cell compartment in the adult intestine (31). Whereas specific roles for these additional laminins on enterocytes still need to be elucidated, it appears more and more evident that the regional localization of individual laminins along the intestinal crypt-villus unit is of importance for the regulation of normal intestinal cell functions.…”
mentioning
confidence: 79%
“…In the human intestine, the three constituent chains of laminin-5 have been detected in the subepithelial basement membrane concomitant with laminin-1, as early as 8 weeks of gestation. In parallel to the formation of villi, and up to the adult stage, laminin-5 is progressively expressed according to an increasing gradient from the crypt mouth to the villus tip, and is absent from the BM lining the proliferative cells in the crypts Leivo et al 1996). The distribution of laminin-5 individual chains in the mouse intestine is somewhat di¡erent from that found in human: at early stages of development only g 2 and b 3 chains are found; in the adult intestine a 3 and b 3 chains are restricted to the very top of the villi, where the most di¡erentiated cells that will be extruded into the lumen are found.…”
Section: Expression and Role Of Laminin Isoforms In The Intestinementioning
confidence: 99%